The practical handbook of library architecture creating building spaces that work - Schlipf, Frederick A.; Moorman, John A. (ALA Editions, 2018)
Distilling hard fought wisdom gleaned from hundreds of successful library construction projects they've supervised or coordinated, the authors present this definitive resource on library architecture. With a special emphasis on avoiding common problems in library design, in a down-to-earth manner they address a range of issues applicable to any undertaking. From planning completely new library buildings to small remodeling projects, they offer specific how-to and how-not-to guidance